Sensitivity of the Molecular Test in Saliva for Detection of COVID-19 in Pediatric Patients With Concurrent Conditions - Ana Laura, Guzmán-Ortiz; Abraham Josué, Nevárez-Ramírez; Briceida, López-Martínez; Israel, Parra-Ortega; Tania, Angeles-Floriano; Nancy, Martínez-Rodríguez; Lourdes, Jamaica-Balderas; Daniela, De la Rosa-Zamboni; Fernando, Ortega-Riosvelasco; Carlos Mauricio, Jaramillo-Esparza; Sergio René, Bonilla-Pellegrini; Irineo, Reyna-Trinidad; et al. (Frontiers in Pediatrics, 2021)
Background: The reference standard for the molecular diagnostic testing for COVID-19 is the use of nasopharyngeal or combined nasopharyngeal and oropharyngeal (NP/OP) swabs. Saliva has been proposed as a minimally invasive specimen whose collection reduces the risks for health care personnel. Objective: To assess the suitability of saliva for COVID-19 diagnosis as a replacement of the reference standard NP/OP swab in the setting of a tertiary care pediatric unit. Study design: A paired study based in the prospective cohort design in patients suspected of having COVID-19. Methods: RT-PCR was used to detect SARS-CoV-2 in paired samples of saliva and NP/OP swab collected from May through August 2020 from 156 pediatric participants, of whom 128 has at least one comorbidity and 91 showed clinical symptoms related to SARS-CoV-2 infection. Additionally, we studied a group of 326 members of the hospital staff, of whom 271 had symptoms related to SARS-CoV-2 infection. Results: In the group of pediatric participants the sensitivity of the diagnostic test in saliva was 82.3% (95% CI 56.6 – 96.2) and the specificity 95.6% (95% CI 90.8 – 98.4). The prevalence of COVID-19 was 10.9% (17/156). In 6 of the 23 participants who tested positive for SARS-CoV-2 in at least one specimen type, the virus was detected in saliva but not in NP/OP swab, while in 3 participants the NP/OP was positive and saliva negative. In the group of adults, the sensitivity of the test in saliva was 77.8% (95% CI 67.2 – 86.3) and prevalence 24.8% (81/326). Discordant results between the two types of specimens showed a significant association with low viral load in the pharynx of adults but not of pediatric participants. Interpretation: In the context of a pediatric tertiary care hospital, the sensibility of the test in saliva is not high enough to replace the use of NP/OP swab for COVID-19 diagnosis. Neither NP/OP swab nor saliva could detect all the participants infected with SARS-CoV-2.